2021
DOI: 10.33448/rsd-v10i11.18052
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organo-mineral supplementation on the production of secondary metabolites in in vitro-germinated Bromelia balansae Mez.

Abstract: This work details the investigation of the influence of organo-mineral supplementation on the production of secondary metabolites in in vitro-germinated Bromelia balansae Mez. The seeds were germinated in vitro and transplanted to standard soils to undergo organo-mineral supplementation. The fully-grown plants were subjected to qualitative phytopharmacological prospection; quantitative analysis of total phenols and flavonoids; as well as chemical profiling by mass spectrometry. The in vitro germination of B. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has been reported that subtle variations in soil pH and humidity significantly affect wines' final flavour and aroma profile [5]. Several feedback mechanisms depend on environmental conditions, as proven elsewhere [6,7], regulating the production of secondary metabolites. Likewise, wine astringency is deeply affected by mechanic disturbances on the plant, hence the role of polyphenolic compounds such as tannins in hindering the animal foraging of plant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that subtle variations in soil pH and humidity significantly affect wines' final flavour and aroma profile [5]. Several feedback mechanisms depend on environmental conditions, as proven elsewhere [6,7], regulating the production of secondary metabolites. Likewise, wine astringency is deeply affected by mechanic disturbances on the plant, hence the role of polyphenolic compounds such as tannins in hindering the animal foraging of plant tissues.…”
Section: Introductionmentioning
confidence: 99%